T Cell Dysfunction in Cancer Immunity and Immunotherapy - Xia, Anliang; Zhang, Yan; Xu, Jiang; Yin, Tailang; Lu, Xiao-Jie (Frontiers in Immunology, 2019)
In cancer, T cells become dysfunctional owing to persistent antigen exposure. Dysfunctional T cells are characterized by reduced proliferative capacity, decreased effector function, and overexpression of multiple inhibitory receptors. Due to the presence of various inhibitory signals in the complex tumor microenvironment, tumor-specific T cells have distinct dysfunction states. Therapeutic reactivation of tumor-specific T cells has yielded good results in cancer patients. Here, we review the hallmarks of T cell dysfunction in cancer. Also, we discuss the relationship between T cell dysfunction and cancer immunotherapy.